Facile synthesis of imidazo[1,2-a]pyridines promoted by room-temperature ionic liquids under ultrasound irradiation - Piyawat Paengphua (2018)
© 2018, Springer-Verlag GmbH Austria, part of Springer Nature. Abstract: A simple and efficient procedure for the synthesis of substituted imidazo[1,2-a]pyridines under ultrasound irradiation has been developed. The reactions were carried out using ionic liquids as catalyst. The reaction procedure demonstrated a broad substrate scope for both acetophenones and 2-aminopyridines, and provided convenient access to a wide variety of imidazo[1,2-a]pyridines. The present method offers several advantages compared to traditional heating methods such as higher yields, shorter reaction times, milder reaction conditions, and easier work-up procedure. Graphical abstract: [Figure not available: see fulltext.].